Review of Implementation Living Values Education Program in Strengthening Education in PAUD Amanah Kahmi - Syahputra, M Romi; Nazriani, Dina; Balqis, Muthia Ferliani (Talenta Publisher Universitas Sumatera Utara, 2023)
In general, this school needs learning assistance equipment to support learning that can help active learning. The Covid-19 pandemic has disrupted the conventional learning process. So, a solution is required to answer this problem. The purpose of the service is to reduce the deficiencies in the implementation of learning in PAUD AMANAH KAHMI SUMUT. Character education is essential to become the leading mainstream of education in Indonesia both in the formal, non-formal and informal realms. Several factors affect the development of children's character, including parenting style and genetic personality. This study aims to determine the effect of parenting style and genetic personality on children's character development.